Unheroic conduct : the rise of heterosexuality and the invention of the Jewish man - Boyarin, Daniel (Contraversions, 1997)
"The Western notion of the aggressive, sexually dominant male and the passive female, as Daniel Boyarin makes clear, is not universal. Analyzing ancient and modern texts, he recovers the studious and gentle rabbi as the male ideal and the prime object of the female desire in traditional Jewish society. Challenging those who view the "feminized Jew" as a pathological product of the Diaspora or a figment of anti-Semitic imagination, Boyarin finds the origins of the rabbinic model of masculinity in the Talmud. The book provides an unrelenting critique of the oppression of women in rabbinic society, while also arguing that later European bourgeois society disempowered women even further. Boyarin also analyzes the self-transformation of three iconic Viennese modern Jews: Sigmund Freud, Theodor Herzl, and Bertha Pappenheim (Anna O.). Pappenheim is Boyarin's hero: it is she who provides him with a model for a militant feminist, anti-homophobic transformation of Orthodox Jewish society today."--Jacket